2018
DOI: 10.1002/cbdv.201800005
|View full text |Cite
|
Sign up to set email alerts
|

Response of Biomass Development, Essential Oil, and Composition of Plectranthus amboinicus (Lour.) Spreng. to Irrigation Frequency and Harvest Time

Abstract: A greenhouse experiment was conducted to study the effects of four irrigation intervals (4, 8, 12, and 16 days) and six harvests (2, 4, 6, 8, 10, and 12 months after transplanting) on biomass, essential oil content, and composition of Plectranthus amboinicus (Lour.) Spreng. Fresh weight and essential oil yield decreased with increasing irrigation interval; whereas, essential oil content was stimulated by water stress and increased as the irrigation interval increased. Fresh weight of Plectranthus amboinicus ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In other species, PA extract improved the nonspecific immune response and growth performance in white‐leg shrimp (Huang et al, 2022). This herbal essential oil has the main bioactive compounds of carvacrol (Murthy et al, 2009) and thymol (Sabra et al, 2018), which can be compared with thyme and oregano EOs. Rosemary ( Rosmarinus officinalis L.) is another aromatic plant from the Lamiaceae family with the main components including camphor, 1,8‐cineole, and α‐pinene (Sienkiewicz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In other species, PA extract improved the nonspecific immune response and growth performance in white‐leg shrimp (Huang et al, 2022). This herbal essential oil has the main bioactive compounds of carvacrol (Murthy et al, 2009) and thymol (Sabra et al, 2018), which can be compared with thyme and oregano EOs. Rosemary ( Rosmarinus officinalis L.) is another aromatic plant from the Lamiaceae family with the main components including camphor, 1,8‐cineole, and α‐pinene (Sienkiewicz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of harvest time and its effect on the quantity and quality of essential oil was studied by several researchers including Court et al (1993), andCarvalho Filho et al (2006). Previous studies showed that the time of harvest is an important factor that influences the quantity and quality of essential oil from herbal plants, and that the ideal harvest time varies with the plant and with what was harvested (Mahmoud et al, 2018;Sabra et al, 2018;Said-Al Ahl et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The same was observed by May et al (2008) for lemongrass (Cymbopogon flexuosus Stapf.). However, Sabra et al (2018) reported an increase in the phytomass of Indian borage [Plectranthus amboinicus (Lour.) Spreng.]…”
Section: Introductionmentioning
confidence: 99%